Desempenho produtivo e fisiológico do rabaneteiro em consorciação com espécies aromáticas e condimentares - Lima Neto, Benedito Pereira (2020)
The intercropping allows to improve the utilization of the cultivation area and, thus, to increase productivity per unit area. In this sense, the objective of this research was to evaluate the productive and physiological performance of the rabaneteiro in association with aromatic and condiment species. The study was conducted in an experimental area of the Horta Didática of the Universidade Federal do Ceará, in a randomized block design, with four replications and nine treatments: T1 - single cultivation of radish; T2 - intercropping radish and coriander; T3 - intercropped radish and chives; T4 - intercropped radish and nirá cultivation; T5 - intercropping of radish and basil; T6 - single cultivation of coriander; T7 - single cultivation of chives; T8 - single cultivation of nirá and T9 - single cultivation of basil. The following agronomic characteristics were evaluated: average number of leaves, plant height (cm), diameter and length of the tuber (cm), fresh and dry mass of the tuber (g) and total production per area. For biological efficiency were calculated: index of efficient land use, relative contribution of the radish crop to the UET, ratio of area equivalent in time and index of productivity of the system. For the physiological evaluation, liquid photosynthesis, CO2 concentration in the substomatic chamber, instant carboxylation efficiency, ratio between the concentration of CO2 in the substomatic chamber and the concentration of CO2 in the environment, stomatal conductance, transpiration rate and leaf area were measured. For competitive ability, the following indices were calculated: aggressiveness, competition and compensation. In general, the efficiency and the advantage of the intercropped system had an influence on the complementarity between the component cultures. The radish and coriander consortium showed the highest productivity and biological efficiency, with the highest interspecific complementarity. There was no physiological difference between the intercropped and monoculture production systems. There was a difference between the radish production cycles, due to environmental issues. The radish showed greater competitive ability in consortium with coriander and nira. Chives were the most aggressive crop. The radish and nira consortium were the most advantageous, allowing a greater balance in the use of productive resources.